Pembelajaran di Masa Pandemi Bagi Siswa Berkebutuhan Khusus di SD Negeri 5 Lubai - Amir Hamzah; Tastin; Ahmad Syarifuddin; Faisal; Dhea Ardelia Tifani (IBTIDA', 2021)
This study aims to determine the implementation of learning for students with special needs at SDN 5 Lubai during the covid 19 pandemic. several sata, namely through observation, interviews, and document analysis. The implementation of learning activities during this pandemic is still running through distance learning with online media in accordance with the provisions of schools and the government. The teaching and learning process during the pandemic is carried out online to prevent and also minimize physical contact between teachers and students so that they can inhibit and stop the spread of the Covid virus: 19